1993
DOI: 10.1161/01.cir.88.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age and hemodynamics on myocardial blood flow and flow reserve.

Abstract: Aging does not alter significantly dipyridamole-induced hyperemic flows; although coronary vascular resistance after dipyridamole was somewhat increased in older subjects. The gradual decline of the myocardial blood flow reserve correlates with an age-related increase of baseline myocardial work and blood flow. These findings suggest that the reduced flow reserve with age is primarily due to increased cardiac work and blood flow at rest rather than to an abnormal vasodilator capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
226
5
5

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 431 publications
(261 citation statements)
references
References 35 publications
25
226
5
5
Order By: Relevance
“…[65][66][67][68][69][70][71] Apart from methodologic differences in radiotracer characteristics, tracer kinetic models, and image analysis that may introduce some variations between different studies, the variability of the reported resting MBF values may be attributed in part to differences in myocardial workload and thus the myocardial oxygen demand of the left ventricle. 66,67,[72][73][74] Sex and genetic variations, including mitochondrial function, are also important determinants contributing to the variability in resting MBF values. 75 MBF at rest and during some forms of stress is physiologically coupled with myocardial oxygen demand and thus correlates with indices of myocardial workload (e.g., rate-pressure product, defined as the product of systolic blood pressure and heart rate).…”
Section: Resting Mbfmentioning
confidence: 99%
See 3 more Smart Citations
“…[65][66][67][68][69][70][71] Apart from methodologic differences in radiotracer characteristics, tracer kinetic models, and image analysis that may introduce some variations between different studies, the variability of the reported resting MBF values may be attributed in part to differences in myocardial workload and thus the myocardial oxygen demand of the left ventricle. 66,67,[72][73][74] Sex and genetic variations, including mitochondrial function, are also important determinants contributing to the variability in resting MBF values. 75 MBF at rest and during some forms of stress is physiologically coupled with myocardial oxygen demand and thus correlates with indices of myocardial workload (e.g., rate-pressure product, defined as the product of systolic blood pressure and heart rate).…”
Section: Resting Mbfmentioning
confidence: 99%
“…[76][77][78] Consequently, resting MBF is commonly higher in patients with higher arterial blood pressure or heart rate. 67,70,79,80 Age-related increases in resting MBF can be explained by rate-pressure product correction of increased systolic blood pressures. 67,81 Most of the reported PET-determined resting MBF values have been higher in women than in men.…”
Section: Resting Mbfmentioning
confidence: 99%
See 2 more Smart Citations
“…Baseline MBF is closely related to baseline RPP15; thus, baseline MBF was corrected for baseline RPP using the formula baseline MBF corrected =baseline MBF/(baseline RPP/10 000), to account for differences in cardiac work, as previously described 6. In accordance with previous studies, adenosine‐stress–induced MBF was not corrected because this parameter is grossly independent of RPP 16.…”
Section: Methodsmentioning
confidence: 94%